Modelling of wall panels and vertical joints between them for pushover analysis of a precast wall type building - Biswal, Aparup; Reddy, K.V. Snehalatha; Sengupta, Amlan Kumar; Prasad, A. Meher (Journal of Structural Engineering, 2024)
In a precast concrete wall type building, the joints between the precast wall panels are critical interfaces of forcetransfer. This paper investigates the influence of modelling the grouted vertical joints (considered to be emulativejoints) between the wall panels on the behaviour of a building under lateral loads. To quantify the influence, threedifferent types of models were investigated (i) monolithic model without considering the joints, (ii) walls with gapsfor the joints and (iii) walls with shear link: elements for the joints. Next, two different modelling approaches wereconsidered: (i) reference models using two-dimensional (2D) membrane elements and (ii) simplified models using onedimensional(1D) equivalent column elements. Nonlinear static pushover analysis was carried out on standalone wallpanel assemblages (with and without openings) and on a typical midrise building. To capture the material nonlinearityunder increasing roof displacement (drift), multi-layered membrane elements and point plasticity in the columnelements were used for the two types of models, respectively. From the observed results, it was found that a modelwith gaps for the joints gives an overestimation of drift and conservative estimation of lateral strength comparedto the model with link elements. Also, it was observed that the behaviour of a wall panel assemblage modelled usingcolumn elements was comparable to that of a model using membrane elements till the peak strength, with acceptablevariation in the post-peak behaviour. Hence, it can be inferred that a model using column elements for the panels andlink elements for the joints as demonstrated in this paper, is suitable for the pushover analysis of large buildings madeof precast wall panels.